Identification of an inducible factor that binds to a positive regulatory element of the human beta-interferon gene. - Keller, A D (1988)
Human beta-interferon gene expression is induced by virus or poly(I).poly(C). This induction is due at least in part to an increase in the rate of transcription and does not require protein synthesis. A 40-base-pair DNA sequence within the beta-interferon promoter, termed the interferon gene regulatory element (IRE), is an inducible enhancer in mouse fibroblasts, and both positive and negative regulatory DNA sequences have been identified within this element. In this paper we identify three factors that bind specifically to two positive regulatory domains within the IRE. Two of these factors are present in nuclear extracts prepared from uninduced and induced cells; one is present only in extracts from induced cells. The functional significance of these binding activities was demonstrated by showing that point mutations within the IRE that decrease human beta-interferon gene transcription in vivo prevent binding in vitro. We propose that induction of the beta-interferon gene involves the modification of a protein to a form that binds specifically to a positive regulatory sequence within the IRE.